2014
DOI: 10.1021/nl501850m
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Imaging and Spectroscopy of Multipolar Plasmonic Resonances in Aluminum Nanoantennas

Abstract: We report on the high resolution imaging of multipolar plasmonic resonances in aluminum nanoantennas using electron energy loss spectroscopy (EELS). Plasmonic resonances ranging from near-infrared to ultraviolet (UV) are measured. The spatial distributions of the multipolar resonant modes are mapped and their energy dispersion is retrieved. The losses in the aluminum antennas are studied through the full width at half-maximum of the resonances, unveiling the weight of both interband and radiative damping mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(134 citation statements)
references
References 43 publications
3
131
0
Order By: Relevance
“…The MNPBEM code developed by Hohenester and Trügler [89][90][91], which in recent years has been extensively used for the simulation of plasmonic nanoparticles [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108], is used for these simulations. Further details can be found in Sec.…”
Section: Numerical Methods and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The MNPBEM code developed by Hohenester and Trügler [89][90][91], which in recent years has been extensively used for the simulation of plasmonic nanoparticles [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108], is used for these simulations. Further details can be found in Sec.…”
Section: Numerical Methods and Theorymentioning
confidence: 99%
“…REV. APPLIED 9, 064038 (2018) 064038-10 plasmonic excitations in the nanoparticles studied here from the collected experimental STEM-EELS data (as was also done by other groups for other NPs [46,102,119,120] Figure 7 shows the dipolar plasmonic mode energies of all 66 studied nanoparticles versus their aspect ratio A ¼ L=w (where L is the length and w the width of the nanoparticle). The results of different length ranges of the nanoparticles (L < 30 nm, 30 nm < L < 60 nm, 60 nm < L < 90 nm, and 90 nm < L) are coded with different colors (dark blue, green, orange, and light blue) in Fig.…”
Section: Experimental and Analytical Plasmonic Dispersion Relationmentioning
confidence: 97%
“…The boundary element method (BEM) numerical simulations are achieved using either BEM-3D 37 or the MNPBEM toolbox 53 with its EELS/CL extension, 54 with the CL spectra computed as described in ref 55. Simulations including a substrate are performed by adding a 5 nm thin cylinder upon which the nanoprism stands completely.…”
Section: Nano Lettersmentioning
confidence: 99%
“…Among these methods are lithography, laser ablation and chemical synthesis. This includes nanorods [28][29][30], nanodisks [22] or flat triangles [31,32]. The main disadvantage is its inherent high tendency to oxidation.…”
Section: Aluminummentioning
confidence: 99%
“…This is why this oxide layer is sometimes described as a "protective" layer. Recent experiments on Al nanorods, have shown that high-order resonant modes are more confined inside the oxide-shell [30].…”
Section: Aluminummentioning
confidence: 99%